Using profile of pysicotropic medicines distributed by public pharmacies during the COVID-19 pandemic (Research, Society and Development, 2022)
Introduction: COVID-19 brought with it several consequences, among them the increase in cases of mental health disorders, and also the pattern of consumption of psychotropic drugs by the population. Objective: to analyze possible changes in the consumption of psychotropic drugs used before and during the pandemic in family pharmacies in the city of Vitória da Conquista - Bahia, as well as the profile of the population that used it during the aforementioned periods. Materials and Methods: this is a cross-sectional study of a quantitative nature. The study data were obtained through the HORUS system - National Pharmaceutical Assistance Management System, where a survey was carried out on the number of patients who used psychotropic drugs in the years 2018, mid-2020 and until December 2021. general characteristics such as sex, age, as well as the origin of the prescriptions were evaluated. Results: There was a high number of prescriptions in the period collected, the majority from the SUS (n=86731, r=86.8%). The most prevalent drugs were fluoxetine (16.3%), Clonazepam (16.3%), Carbamazepine (15.5%) and Risperidone (11.5%). Regarding gender, 57.7% of prescriptions were directed to female patients, with a middle age of 49.7 years (±16.1 years) and males: 42.8 years (±18.6 years) . There was a statistically significant association with increased use of fluoxetine among women during the pandemic. Final considerations: It was found that there was a significant increase in the demand for psychotropic drugs during the pandemic, especially among female patients.